Urgensi Literasi Keuangan di Kalangan Mahasiswa Pendidikan IPS UIN Malang - Nabila Harumnike Azzahroh; Rahma Putri Andini; Indri Damaiyanti (Universitas Negeri Makassar, 2026)
Financial literacy is a very important skill that students must have in order to face the challenges of personal financial management in the era of digitalization. This article examines the urgency of financial literacy among students majoring in social sciences at UIN Malang. With the increasing potential risks of improper financial management, this study highlights the importance of understanding financial literacy as an effort to support student welfare. The research method used was a survey of PIPS UIN Malang students, which was then analyzed to determine the level of literacy and its impact on personal financial management. The results showed that adequate financial literacy can help students reduce consumptive behavior, improve long-term financial planning skills, and manage finances effectively. This article explains that there needs to be an emphasis on integrating financial literacy education into the curriculum and mentoring programs to equip PIPS UIN Malang students to face future financial challenges.